Leukotriene Production Is Increased in Abdominal Obesity - Bäck, Magnus; Avignon, Antoine; Stanke-Labesque, Françoise; Boegner, Catherine; Attalin, Vincent; Leprieur, Elodie; Sultan, Ariane (PloS one, 2014)
Obesity is a major risk factor for insulin resistance and type-2 diabetes. A chronic low grade inflammatory state has been described during obesity and associated with insulin resistance pathogenesis. Results from animal studies are in favor of a role of the leukotriene (LT) pathway in obesity induced-insulin resistance. However, there is a paucity of data regarding this association in human obesity. Therefore, the aim of this study was to investigate whether LT production was associated with insulin resistance and other metabolic parameters in a cohort of obese subjects. Forty-six (70% females) obese subjects (BMI≧30 kg/m2) without known diabetes and without inflammatory disease (CRP<10 mg/l) were included. Median age was 44 years (16-80) with a median BMI of 36.8 kg/m2 (30-51). Insulin resistance was evaluated by HOMA-IR index and glucose tolerance test. Urinary LTE4 (U-LTE4) concentration was measured by enzyme immune assay. Screening for obstructive sleep apnea was performed. There was a positive association of U-LTE4 with waist to hip ratio, systolic blood pressure and HOMA-IR in univariate analysis. Further, waist to hip ratio remained the only parameter significantly correlated with U-LTE4, in adjusted multivariate analysis. Taken together, these results confirm the previously established notion of chronic low grade inflammation in obesity and further suggests a role for the LT pathway in obesity-associated development of insulin resistance in humans.